Distribution and habitat preferences of Hippocampus species along the Apulian coast. Issue 6 (9th August 2018) - Lazic, Tamara; Pierri, Cataldo; Gristina, Michele; Carlucci, Roberto; Cardone, Frine; Colangelo, Paolo; Desiderato, Andrea; Mercurio, Maria; Bertrandino, Marta Simona; Longo, Caterina; Carbonara, Pierluigi; Corriero, Giuseppe
Abstract: The aim of this study was to provide further knowledge of the ecological, spatial, and temporal distribution and life‐cycle traits of the sympatric seahorse species Hippocampus hippocampus and Hippocampus guttulatus . From 2011 to 2014, data were collected from 20 sites along the Apulian coast (Southern Italy) in order to cover a wide range of coastal marine, open water, and lagoon sites, from the surface to a depth of 48 metres. Seahorses were found at seven of the 20 sites investigated. Both species displayed temporal persistence, patchy distribution, and a high spatial demographic heterogeneity. This study revealed a smaller maximum size and size at maturity of H. guttulatus than has been reported elsewhere. Although it is possible that environmental factors are influencing the size of these animals, there may be genetic explanations, especially for lagoon populations. Despite the fragmented distribution and often low abundance found along the Apulian coast, some seahorse populations appear to be locally persistent and stable over time, suggesting that there is a need for appropriate location‐specific conservation strategies. Not just maintaining but increasing the area of artificial substrates, which enhance habitat complexity and provide holdfasts, could represent a possible approach to help conserve marine littoral biodiversity and to protect endangered species in lagoons.